Diffusion Layer
The diffusion layer addresses the high cost and performance issues in existing technologies by using M-Ti oxide and precious metal coatings on a porous substrate, achieving excellent corrosion resistance and conductivity with reduced precious metal usage.
Patent Information
- Application Number
- JP2021190021
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-11-24
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2041-11-24
AI Technical Summary
Existing diffusion layers in solid polymer fuel cells and PEM water electrolysis devices face challenges with high cost due to the use of expensive precious metals and inefficient manufacturing processes, while also struggling with corrosion and electrical conductivity issues.
A diffusion layer comprising a porous substrate with a first coating of M-Ti oxide on one surface and a second coating of precious metal, alloy, or oxide on the other surface, formed using low-cost dry film formation methods like sputtering.
The diffusion layer achieves excellent corrosion resistance and electrical conductivity while significantly reducing the amount of precious metals used, resulting in a lower-cost fuel cell and water electrolysis system.
Smart Images

Figure 0007669910000001 
Figure 0007669910000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a diffusion layer, and more specifically to a diffusion layer used in a gas diffusion layer of a polymer electrolyte fuel cell (PEFC) or a gas diffusion layer of a polymer electrolyte membrane (PEM) water electrolysis device. [Background technology]
[0002] A polymer electrolyte fuel cell is equipped with a membrane electrode assembly (MEA) in which electrodes (catalyst layers) containing a catalyst are bonded to both sides of an electrolyte membrane. Gas diffusion layers (GDLs) are arranged on both sides of the MEA, and separators (also called current collectors) equipped with gas flow paths are arranged on the outside of the GDLs. A polymer electrolyte fuel cell usually has a structure (fuel cell stack) in which a plurality of unit cells each consisting of an MEA, a gas diffusion layer, and a separator are stacked. When a fuel gas and an oxidant gas are supplied to the anode and cathode of such a fuel cell, respectively, water is produced at the cathode and electricity is simultaneously extracted.
[0003] On the other hand, PEM water electrolysis devices have a structure similar to that of polymer electrolyte fuel cells, but they induce the opposite reaction to that of polymer electrolyte fuel cells. That is, when water is supplied to the oxygen electrode and electricity is supplied between the electrodes, the water is electrolyzed and hydrogen and oxygen can be extracted.
[0004] In a PEM water electrolysis device, the gas diffusion layer is also called a porous transport layer (PTL). In the present invention, the term "diffusion layer" refers to these collectively, that is, to the member inserted between the MEA and the separator, regardless of the application of the MEA.
[0005] In solid polymer electrolyte fuel cells and PEM water electrolysis devices, polyperfluorocarbon sulfonic acid membranes are usually used as electrolyte membranes. Therefore, the diffusion layer is exposed to a strong acidic atmosphere during use. If the surface of the diffusion layer is oxidized during use and a high resistance layer is formed on the contact surface with the electrode (catalyst layer) or separator, the electrode reaction or electrolysis reaction is inhibited.
[0006] In order to solve this problem, various proposals have been made in the past. For example, Non-Patent Document 1 discloses an anode gas diffusion layer for a PEM water electrolysis cell made of Pt-coated porous titanium. The document states that since the anode side has a high potential, the surface of the anode gas diffusion layer made of titanium needs to be coated with Pt in order to improve durability.
[0007] As described in Non-Patent Document 1, coating the surface of porous titanium with Pt improves the corrosion resistance of the anode gas diffusion layer. However, the method described in Non-Patent Document 1 is expensive because it uses an expensive precious metal (Pt).
[0008] Conventionally, plating has been used to coat the anode gas diffusion layer with Pt. (a) Because it is a wet process, it requires a multi-step process, including pre-treatment (e.g., roughening the surface) to make it easier to plate, and post-treatment such as cleaning. (b) The utilization rate of expensive precious metal raw materials is low, resulting in a wasteful and expensive process. (c) In order to completely cover the entire surface of the porous Ti substrate with a Pt coating, the thickness of the Pt coating needs to be about 1 μm. There were problems such as: Furthermore, there has been no conventional proposal for a diffusion layer that can be manufactured by significantly reducing the amount of expensive materials such as precious metals used and without using high-cost processes. [Prior art documents] [Non-patent literature]
[0009] [Non-Patent Document 1] Special feature SPECIAL REPORTS, Toshiba Review, Vol.73, No.3 (May 2018) 9-12, "Precious metal saving electrode for PEM water electrolysis" Summary of the Invention [Problem to be solved by the invention]
[0010] An object of the present invention is to provide a diffusion layer which is excellent in corrosion resistance and electrical conductivity and which is also low in cost. [Means for solving the problem]
[0011] In order to solve the above problems, the diffusion layer according to the present invention comprises: A porous substrate made of a conductive material; a first coating including an M-Ti oxide (wherein M is a trivalent or pentavalent metal element other than Ti) formed on one surface of the substrate; a second coating film including a precious metal, a precious metal alloy including two or more kinds of precious metal elements, and / or a conductive precious metal oxide formed on the other surface of the substrate; The gist of the invention is that it is equipped with the following: Effect of the Invention
[0012] The separator-side surface of the substrate is exposed to a strong acidic atmosphere, but does not come into direct contact with the MEA, so it does not require as high oxidation resistance as the MEA-side surface. Although M-Ti oxide has inferior oxidation resistance compared to precious metals, it has sufficient corrosion resistance and electrical conductivity to protect the separator-side surface. Furthermore, a coating made of M-Ti oxide can be formed by a relatively low-cost sputtering method. Therefore, by forming a first coating containing M-Ti oxide on the separator side of the substrate and forming a second coating containing a precious metal, a precious metal alloy, and / or a precious metal oxide on the MEA side, a diffusion layer that is highly corrosion-resistant and conductive and also low-cost can be obtained. [Brief description of the drawings]
[0013] [Figure 1] FIG. 2 is a graph showing the relationship between current density and cell voltage for the PEM water electrolysis cells obtained in Example 1 and Comparative Examples 1 to 3. [Diagram 2] FIG. 1 is a diagram showing the relationship between x and electrical conductivity of NbxTi1-xO2+α. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] An embodiment of the present invention will be described in detail below. [1. Diffusion layer] The diffusion layer according to the present invention comprises: A porous substrate made of a conductive material; a first coating including an M-Ti oxide (wherein M is a trivalent or pentavalent metal element other than Ti) formed on one surface of the substrate; a second coating film including a precious metal, a precious metal alloy including two or more kinds of precious metal elements, and / or a conductive precious metal oxide formed on the other surface of the substrate; It is equipped with:
[0015] [1.1. Base material] The substrate is a porous member made of a conductive material. As described above, the diffusion layer is inserted between the MEA and the separator. Therefore, the substrate is (a) Electrical conductivity sufficient to allow electrons to be exchanged between the MEA and the separator; (b) Porosity sufficient to allow the supply of raw materials and fuel from the separator to the MEA and the discharge of reaction products from the MEA to the separator. It is necessary to have the following.
[0016] The material of the substrate is not particularly limited as long as it exhibits the above-mentioned functions. Examples of the material of the substrate include: (a) Metal mesh, foam metal or sintered metal made of various metals such as titanium or titanium alloy, stainless steel, aluminum or aluminum alloy, (b) Porous carbon sheets such as carbon paper and carbon nonwoven fabric; etc.
[0017] Among these, titanium or titanium alloys form a passivation film mainly composed of TiO2 on the surface under oxidizing conditions, which has the advantage that titanium ions and the like are unlikely to be eluted even if part of the substrate surface is exposed. Stainless steel has the advantages of being inexpensive and easy to process. Aluminum, aluminum alloys, and polymeric materials have the advantages of being inexpensive, lightweight, and easy to process.
[0018] [1.2. First coating] [1.2.1. Materials] The first coating contains an M-Ti oxide. In the present invention, the term "M-Ti oxide" refers to an oxide containing Ti and a trivalent or pentavalent metal element M other than Ti.
[0019] The M-Ti oxide is particularly preferably an oxide having a composition represented by the following formula (1). M x Ti 1-x O 2+α …(1) however, M is a trivalent or pentavalent metal element other than Ti; 0.2≦x≦0.8, α is the value at which electrical neutrality is maintained.
[0020] Examples of the metal element M include Nb, Ta, Bi, and V. All of these metal elements M have the effect of improving the corrosion resistance and electrical conductivity of the M-Ti oxide. The M-Ti oxide may contain any one of these metal elements M, or may contain two or more of them.
[0021] In formula (1), x represents the ratio of the number of atoms of the metal element M to the total number of atoms of Ti and the metal element M. If x is too small, the electrical conductivity may decrease. Therefore, x is preferably 0.2 or more. x is preferably 0.3 or more, more preferably 0.4 or more. On the other hand, if x is too large, the electrical conductivity may decrease. Therefore, x is preferably 0.8 or less. x is preferably 0.7 or less, and more preferably 0.6 or less.
[0022] In formula (1), α represents a value that maintains electrical neutrality. For example, when Ti is tetravalent and the metal element M is pentavalent, α can ideally be expressed as α=x / 2. However, in reality, α may deviate from the ideal value due to impurities, oxygen defects, etc.
[0023] Any of the M-Ti oxides having a specific composition has high corrosion resistance in a fuel cell environment or a water electrolysis device environment and high electrical conductivity, and is therefore suitable as a material for the first coating. The first coating may contain any one of these M-Ti oxides, or may contain two or more of them. The M-Ti oxide contained in the first coating is preferably one containing Nb as the metal element M. x Ti 1-x O 2+α ) has both high durability and high conductivity.
[0024] The first coating preferably consists essentially of M-Ti oxide, but may contain other phases as long as they do not impair the high corrosion resistance and high electrical conductivity. Other phases include, for example: (a) unavoidable impurities, (b) Highly corrosion-resistant materials other than M-Ti oxides, etc.
[0025] 1.2.2 Thickness The thickness of the first coating is not particularly limited, and an optimal thickness can be selected depending on the purpose. In general, if the thickness of the first coating is too thin, sufficient corrosion resistance cannot be obtained. Therefore, the thickness of the first coating is preferably 30 nm or more. The thickness of the first coating is preferably 40 nm or more, and more preferably 50 nm or more. On the other hand, if the thickness of the first coating is too thick, the adhesion to the substrate decreases, and peeling or cracking may occur. Therefore, the thickness of the first coating is preferably 500 μm or less. The thickness of the first coating is preferably 300 nm or less, and more preferably 200 nm or less.
[0026] [1.2.3. Position of first coating] The first coating is formed on one surface of the substrate. In the present invention, "one surface" refers to the surface on the separator side of a polymer electrolyte fuel cell or a PEM water electrolysis device. The first coating may be formed on the entire one surface of the substrate, or may be formed on only a part of the one surface.
[0027] The separator is usually provided with a flow path for the flow of fuel for power generation, oxidant, raw material for electrolysis, or reaction products. The diffusion layer usually does not contact the separator over the entire surface of one side, but only contacts the protrusions that form the flow path. Even if a high resistance layer is formed on one surface of the substrate that is not in contact with the separator, there is no significant hindrance to the exchange of electrons. Therefore, the first coating may be formed only on the surface of one surface that is in contact with the separator.
[0028] In order to suppress an increase in contact resistance due to the formation of a high-resistance layer, the first coating preferably covers 90% or more of the contact surface with the separator on one side of the substrate. The first coating preferably covers 95% or more, more preferably 99% or more of the contact surface with the separator. The first coating preferably completely covers the contact surface with the separator.
[0029] [1.3. Second coating] [1.3.1. Materials] The second coating contains a precious metal, a precious metal alloy containing two or more kinds of precious metal elements, and / or a conductive precious metal oxide. The second coating is formed on the surface of the substrate facing the MEA. The reason why the second coating is made of a precious metal, a precious metal alloy, and / or a precious metal oxide is that the second coating is required to have higher corrosion resistance than the first coating.
[0030] Specific examples of the material for the second coating include: (a) a precious metal selected from Au, Ag, Pt, Pd, Rh, Ir, Ru, and Os; (b) Precious metal alloys containing two or more precious metal elements, such as Pt-Pd alloys, Pt-Rh alloys, Pt-Ir alloys, Pd-Ir alloys, and Pt-Au alloys; (c) Conductive precious metal oxides such as platinum oxide, rhodium oxide, iridium oxide, and palladium oxide etc. The second coating may contain any one of these, or may contain a mixture of two or more of them. In particular, the second coating is preferably made of Pt or Au, since these have high corrosion resistance and electrical conductivity.
[0031] The second coating preferably consists essentially of a precious metal, a precious metal alloy, and / or a precious metal oxide, but may contain other phases as long as they do not impair the high corrosion resistance and high electrical conductivity. Other phases include, for example: (a) unavoidable impurities, (b) Highly corrosion-resistant materials other than precious metals, precious metal alloys, and precious metal oxides; etc.
[0032] Thickness The thickness of the second coating is not particularly limited, and an optimal thickness can be selected according to the purpose. In general, if the thickness of the second coating is too thin, sufficient corrosion resistance cannot be obtained. Therefore, the thickness of the second coating is preferably 30 nm or more. The thickness of the second coating is preferably 40 nm or more, and more preferably 50 nm or more. On the other hand, if the thickness of the second coating is too thick, the adhesion to the substrate decreases, and peeling or cracking may occur. In addition, if the thickness of the second coating is too thick, the cost increases. Therefore, the thickness of the second coating is preferably 500 μm or less. The thickness of the second coating is preferably 300 nm or less, and more preferably 200 nm or less.
[0033] [1.3.3. Position of forming the second coating] The second coating is formed on the other surface of the substrate. In the present invention, the "other surface" refers to the surface on the MEA side of the polymer electrolyte fuel cell or PEM water electrolysis device. The diffusion layer usually has a size equal to or larger than that of the catalyst layer of the MEA. Furthermore, no gap is usually intentionally formed between the MEA and the diffusion layer. Therefore, the second coating is preferably formed on 90% or more of the other surface of the substrate. The second coating preferably covers the entire surface of the other surface.
[0034] In order to suppress an increase in contact resistance due to the formation of a high resistance layer, the second coating preferably covers 90% or more of the contact surface with the MEA of the other surface of the substrate. The second coating preferably covers 95% or more, more preferably 99% or more of the contact surface with the MEA. The second coating preferably completely covers the contact surface with the MEA.
[0035] [1.4. Purpose] The diffusion layer according to the present invention comprises: (a) Anode side gas diffusion layer or cathode side gas diffusion layer for a polymer electrolyte fuel cell (b) Oxygen electrode side gas diffusion layer or hydrogen electrode side gas diffusion layer for PEM water electrolysis device It can be used in the following ways: The diffusion layer according to the present invention is particularly suitable as an oxygen electrode side gas diffusion layer of a PEM water electrolysis device. Since the oxygen electrode side gas diffusion layer is exposed to a high potential, application of the diffusion layer according to the present invention to the oxygen electrode side gas diffusion layer can improve the durability of the PEM water electrolysis device.
[0036] [2. Manufacturing method of the diffusion layer] The method for producing a diffusion layer according to the present invention comprises the steps of: A first step of forming a first coating containing M-Ti oxide on one surface of a substrate by using a dry coating method (A); a second step of forming a second coating film containing a precious metal, a precious metal alloy containing two or more kinds of precious metal elements, and / or a conductive precious metal oxide on the other surface of the substrate by using a dry coating method (B); It is equipped with:
[0037] [2.1. 1st step] First, a first coating containing M-Ti oxide is formed on one surface of a substrate by using a dry coating method (A) (first step). In the present invention, the type of dry coating method (A) is not particularly limited as long as it is capable of forming a first coating that is free of pinholes and has a thin and uniform thickness. Examples of the dry coating method (A) include a sputtering method, a PVD method, an ion plating method, and a vapor deposition method. In particular, sputtering is suitable as a method for forming the first coating because it can form a thin and uniform first coating at low cost and can easily form a film over a large area.
[0038] [2.2. 2nd process] Next, a second coating containing a precious metal, a precious metal alloy containing two or more kinds of precious metal elements, and / or a conductive precious metal oxide is formed on the other surface of the substrate using a dry coating method (B) (second step). In the present invention, the type of dry coating method (B) is not particularly limited as long as it is capable of forming a second coating that is free of pinholes and has a thin and uniform thickness. Examples of the dry coating method (B) include a sputtering method, a PVD method, an ion plating method, and a vapor deposition method. The dry coating method (B) may be the same as or different from the dry coating method (A). In particular, sputtering is suitable as a method for forming the second coating because it allows a thin and uniform second coating to be formed at low cost and also makes it easy to form a film over a large area.
[0039] [2.3. Third step] The method for producing a diffusion layer according to the present invention includes the steps of: A third step of heat-treating the first coating at a temperature of 500° C. to 800° C. in an inert atmosphere or a reducing atmosphere to improve the crystallinity of the M-Ti oxide. It may further comprise:
[0040] When the first coating is formed using the dry film formation method (A), the crystallinity of the first coating may decrease, and the electrical conductivity may decrease. On the other hand, when the first coating is formed and then heat-treated, the crystallinity of the first coating may improve. Furthermore, the crystallinity of the M-Ti oxide may be improved by the heat treatment, and the electrical conductivity of the first coating may be further improved. Therefore, the first coating may be heat-treated as necessary.
[0041] It is preferable to select the optimum heat treatment temperature depending on the purpose. In general, if the heat treatment temperature is too low, the heat treatment cannot be completed within a practical time. Also, the crystallinity of the M-Ti oxide may not be improved. Therefore, the heat treatment temperature is preferably 500°C or higher. The heat treatment temperature is preferably 600°C or higher, more preferably 650°C or higher. On the other hand, if the heat treatment temperature is too high, the substrate may be damaged. Therefore, the heat treatment temperature is preferably 800° C. or less. The heat treatment temperature is preferably 780° C. or less, and more preferably 740° C. or less.
[0042] The heat treatment time is selected optimally depending on the heat treatment temperature. In general, the higher the heat treatment temperature, the shorter the time required to complete the crystallinity improvement treatment of the M-Ti oxide. The suitable heat treatment time is usually about 2 to 10 hours, depending on the heat treatment temperature.
[0043] [3. Effect] The diffusion layers used in polymer electrolyte fuel cells and PEM water electrolysis devices are exposed to a strong acidic atmosphere during use, and therefore require high corrosion resistance. Conventionally, to solve this problem, a Pt coating was formed on both sides of the diffusion layer substrate using a plating method. However, in order to form a coating without pinholes using the plating method, the thickness of the Pt coating needed to be about 1 μm. Therefore, conventional diffusion layers were expensive.
[0044] In contrast, the separator-side surface of the substrate is exposed to a strong acidic atmosphere, but is not in direct contact with the MEA, so it does not require as high oxidation resistance as the MEA-side surface. In addition, M-Ti oxide has inferior oxidation resistance compared to precious metals, but it has both sufficient corrosion resistance and electrical conductivity to protect the separator-side surface. Furthermore, a coating containing M-Ti oxide can be formed by a relatively low-cost sputtering method. Therefore, by forming a first coating containing M-Ti oxide on the separator side of the substrate and forming a second coating containing a precious metal, a precious metal alloy, and / or a precious metal oxide on the MEA side, a diffusion layer that is highly corrosion resistant and conductive and also low cost can be obtained.
[0045] The diffusion layer according to the present invention achieves high corrosion resistance and high electrical conductivity despite using a smaller amount of expensive precious metal than conventional diffusion layers, and therefore makes it possible to provide a low-cost fuel cell system and water electrolysis system. Furthermore, since the coating is formed by a low-cost dry film formation method (eg, sputtering) rather than a high-cost plating method, not only the material cost but also the process cost is low. EXAMPLES
[0046] (Example 1, Comparative Examples 1 to 3) [1. Sample preparation] [1.1. Preparation of oxygen electrode side diffusion layer] 1.1.1. Example 1 The substrate was a Ti mesh. The sputtering targets for the first and second coatings were Nb x Ti1-x O 2+α The targets were filled in a sputtering target holder, and Nb (x=0.5) and Pt were deposited on one side of the Ti mesh (the side facing the separator) by sputtering. x Ti 1-x O 2+α A Pt coating was formed on the other surface (the surface on the MEA side). x Ti 1-x O 2+α The thickness of the coating (x=0.5) and the Pt coating were each 100 nm.
[0047] [1.1.2. Comparative Example 1] A Pt coating was formed on both sides of the Ti mesh by plating, with a thickness of 1 μm on each side.
[0048] [1.1.3. Comparative Example 2] On both sides of the Ti mesh, Nb x Ti 1-x O 2+α A coating (x=0.5) was formed. Nb x Ti 1-x O 2+α The conditions for forming the coating (x=0.5) were the same as those in Example 1.
[0049] [1.1.4. Comparative Example 3] The uncoated Ti mesh was used as the oxygen electrode diffusion layer.
[0050] [1.2. Preparation of water electrolysis cell] An oxygen electrode catalyst sheet was fabricated by adding an ionomer to the oxygen electrode catalyst IrO2, and a hydrogen electrode catalyst sheet was fabricated by adding an ionomer to the hydrogen electrode catalyst platinum / carbon (Pt / C). Next, an oxygen electrode catalyst sheet and a hydrogen electrode catalyst sheet were transferred to both sides of the electrolyte membrane by thermal transfer to fabricate a membrane electrode assembly (MEA). Furthermore, an oxygen electrode side diffusion layer and an oxygen electrode side flow path block (separator) were placed on one side of the MEA, and a hydrogen electrode side diffusion layer and a hydrogen electrode side flow path block (separator) were placed on the other side.
[0051] The oxygen electrode side diffusion layer used was the diffusion layer prepared in [1.1.]. In Example 1, the diffusion layer was installed so that the Pt coating was in contact with the MEA. The oxygen electrode side flow path block used a Pt-plated Ti member. Furthermore, the hydrogen electrode side diffusion layer and the hydrogen electrode side flow path block were each made of a carbon member. After assembling the PEM water electrolysis cell, the airtightness was inspected by a differential pressure test, and then the cell was subjected to a water electrolysis evaluation test.
[0052] 2. Test Method Water electrolysis was performed with the temperature of the PEM water electrolysis cell kept constant at 80°C. Furthermore, the current density was set to 3.0 A / cm 2 The change in cell voltage when the concentration was increased to was measured.
[0053] [3. Results] Fig. 1 shows the relationship between the current density and the cell voltage for the PEM water electrolysis cells obtained in Example 1 and Comparative Examples 1 to 3. The following can be seen from Fig. 1. (1) Example 1 showed a low voltage almost equivalent to that of Comparative Example 1, which used a Pt-plated diffusion layer according to the prior art. In the case of Example 1, the current density was 3.0 A / cm 2 The voltage at 1.7 V was approximately 1.7 V, demonstrating excellent cell characteristics. It was confirmed that even with an increase in current density, there was no increase in resistance due to corrosion, and electrical conductivity and corrosion resistance were maintained.
[0054] (2) By changing the method for forming the Pt coating from plating to sputtering, the thickness of the Pt coating could be reduced to 1 / 10. Furthermore, by coating only one side with Pt, the amount of Pt used could be halved. As a result, the total amount of Pt used could be reduced to 1 / 20. The coverage area in the sputtering method was about a fraction of that in the plating method. That is, in Example 1, the same water electrolysis performance could be achieved with an amount of Pt used that was about two orders of magnitude less than that in Comparative Example 1.
[0055] (3)Nb 0.5 Ti 0.5 O 2+αWhen a Ti mesh diffusion layer with sputtered Ti on both sides was used (Comparative Example 2), the current density was 2.8 A / cm 2 The voltage rose to about 3.0 V at 1000 mAh. In the case of the uncoated Ti mesh diffusion layer (Comparative Example 3), the cell voltage increased rapidly with increasing current density. This is thought to be because an oxide layer with high resistance was formed on the surface due to corrosion, increasing the resistance.
[0056] Example 2 [1. Sample preparation] The sputtering target for the first coating is Nb x Ti 1-x O 2+α An oxygen electrode side diffusion layer was produced in the same manner as in Example 1, except that (x=0 to 1.0) was used.
[0057] [2. Test Method and Results] The sample was pressurized with a pressure of 0.1 MPa using a pressure tool, and the electrical conductivity of the oxygen electrode side diffusion layer was measured using a DC four-terminal method. x Ti 1-x O 2+α 2 shows the relationship between x and electrical conductivity. It can be seen from FIG. 2 that excellent electrical conductivity is exhibited when x is 0.2 to 0.8.
[0058] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the gist of the present invention. [Industrial Applicability]
[0059] The diffusion layer according to the present invention can be used as a gas diffusion layer for a polymer electrolyte fuel cell, a gas diffusion layer for a polymer electrolyte membrane (PEM) water electrolysis device, and the like.
Claims
1. A porous substrate made of a conductive material; a first coating including an M-Ti oxide (wherein M is a trivalent or pentavalent metal element other than Ti) formed on one surface of the substrate; a second coating film formed on the other surface of the substrate, the second coating film including a precious metal, a precious metal alloy including two or more kinds of precious metal elements, and / or a conductive precious metal oxide; Equipped with Used as a gas diffusion layer in a polymer electrolyte fuel cell (PEFC) or a gas diffusion layer in a polymer electrolyte membrane (PEM) water electrolysis cell Diffusion layer. however, The term "one surface" refers to a surface of the polymer electrolyte fuel cell (PEFC) or the polymer electrolyte membrane (PEM) water electrolysis cell facing a separator, The "other surface" refers to the surface of the polymer electrolyte fuel cell (PEFC) or the polymer electrolyte membrane (PEM) water electrolysis cell on the MEA side.
2. 2. The diffusion layer according to claim 1, wherein the M-Ti oxide has a composition represented by the following formula (1): M x Till 1-x Oh 2+α …(1) however, M is a trivalent or pentavalent metal element other than Ti; 0.2≦x≦0.8, α is the value at which electrical neutrality is maintained.
3. The diffusion layer according to claim 1 or 2, wherein M is Nb.
4. The diffusion layer according to claim 1 , wherein the first coating has a thickness of 30 nm to 500 nm.
5. The diffusion layer according to claim 1 , wherein the first coating covers all or a part of one surface of the substrate.
6. The diffusion layer according to claim 1 , wherein the second coating comprises Pt and / or Au.
7. The diffusion layer according to claim 1 , wherein the second coating has a thickness of 30 nm to 500 nm.
8. The diffusion layer according to claim 1 , wherein the second coating covers 90% or more of the other surface of the substrate.
9. 9. The diffusion layer according to claim 1, wherein the substrate is made of titanium or a titanium alloy.
10. The diffusion layer according to claim 1 , wherein the first coating covers 90% or more of a surface of the substrate that is in contact with the separator.
11. 11. The diffusion layer according to claim 1, wherein the second coating covers 90% or more of the surface of the other surface of the substrate that is in contact with the membrane electrode assembly.
Citation Information
Patent Citations
Electrode plate
JP2020152999A
Electrode structure, manufacturing method thereof, and membrane electrode assembly including electrode structure
JP2021103690A
Water electrolysis electrode and water electrolysis apparatus
JP2021155779A
Diffusion layer
JP2022110409A
Electrode for electrolysis, method for producing same, and electrolysis apparatus
WO2013005252A1